Internal dosimetric evaluation of Cu-64-ATSM in canine cancer bearing patients - Bell, Justin James, author; Brandl, Alexander, advisor; Jones, Brian, committee member; Leary, Del, committee member (Colorado State University. Libraries, 2015)
The assessment of the novel radiopharmaceutical Copper-64 diacetyl-bis(N4-methylthiosemicarbazones) (64Cu-ATSMs) ability to selectively accumulate in hypoxic tumor tissue has been subject to ongoing research effort at Colorado State Universitie's (CSU) Veterinary Teaching Hospital (VTH). Due to the unique decay scheme of 64Cu and internal distribution when bound to ATSM, the radiopharmaceutical has clinical importance as a possible Positron Emission Tomography/Computed Tomography (PET/CT) imaging agent with cancer theranostic potential. In this study, the PET/CT images of two cancer bearing canine patients treated with 64Cu-ATSM were used to create patient specific voxelized phantoms that were compatible with the Monte Carlo N Particle extended (MCNPX) radiation transport code which was emplyed to retrospectively assess the internal radiation dose each patient received. By defining specific regions of interest (ROI) within the models, the dose to major organs was estimated. The derived models were designed as to dynamically approximate the relative dose each patient would receive to their tumor and normal tissue if the administered activity of 64Cu-ATSM was altered. From these results, it was identified that the patient's malignances received 64Cu-ATSM uptake at least during the acquisition of the patients' images. Organs such as the liver also had relatively high amounts of 64Cu-ATSM uptake and were used to project what ROI might be dose limiting.